Analisis Pendapatan Petani Cabai Merah di Jalan Alternatif Youtefa Kelurahan Wae Mhorock Distrik Abepura Kota Jayapura - Daniel Ayub Dawan (JURNAL EKONOMI, KEUANGAN, PERBANKAN, KEWIRAUSAHAAN DAN KOPERASI, 2022)
This study aims to determine the income and profit level of cayenne pepper farming in di Jalan Alternatif Youtefa Kelurahan Wae Mhorock Distrik Abepura Kota Jayapura. This research was conducted in di Jalan Alternatif Youtefa Kelurahan Wae Mhorock Distrik Abepura Kota Jayapura from January to March 2020. The research method used the census method. Data collection methods used in the study were direct observation and interviews with sample farmers with the help of a list of questions that had been prepared beforehand as well as documentation and secondary data. The data processing method used in this research is quantitative descriptive analysis. The results showed that the average income obtained by farmers was Rp. 1.843.923 per year and per area cultivated and seen from the R / C> 1, that is, 2,7. This means that the costs incurred are Rp. 4.907.880. will result in an income of Rp. 5.689.687 or 1,99 times the cost, so cayenne pepper farming is profitable for farmers.